STUDENTS' ACADEMIC DISCOURSE FOR PUBLICATION COMPETENCE AND THE REFLECTED IDENTITIES - Wakerkwa, Dian Agustina Purwanto; Kristina, Diah; Rochsantiningsih, Dewi (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
One of the attempts to acquire an identity in the academic community is by participating in the field development by publishing research papers into reputable journals. However, it requires an adequate understanding of the academic discourse for publication. For this concern, the present study aims to investigate the master students' understanding of the term of academic discourse for publication by going through their rejected research articles and their identities reflected from those rejected manuscripts. A qualitative method was employed, the data were gathered through interview of four master students majoring in English Education and the stories are presented narratively. The results show how the students' lack of comprehension of the notion of academic discourse affects their identities as members of the academic community. Pedagogical implications of this study are intended for the master students as the manifestation for their upcoming article’s writing and publication.